THE IMPORTANCE OF A SYNERGISTIC APPROACH IN THE FORMATION OF ECONOMETRIC SKILLS IN STUDENTS - Ravshanova , Xurshida Makhmanazarovna; Ravshanova , Mukhayyo Makhmanazarovna (Innovative Development in Educational Activities, 2024)
This article presents the basic concepts of the synergetic approach in the teaching of econometrics by the researcher and their interrelation, and explains the meanings of these concepts in accordance with the goals and objectives of the study.